Amino Acid Sequence in Constitutionally Isomeric Tetrapeptide Amphiphiles Dictates Architecture of One-Dimensional Nanostructures - Cui, Honggang (American Chemical Society, 2014)
[Image: see text] The switching of two adjacent amino acids can lead to differences in how proteins fold thus affecting their function. This effect has not been extensively explored in synthetic peptides in the context of supramolecular self-assembly. Toward this end, we report here the use of isomeric peptide amphiphiles as molecular building blocks to create one-dimensional (1D) nanostructures. We show that four peptide amphiphile isomers, with identical composition but a different sequence of their four amino acids, can form drastically different types of 1D nanostructures under the same conditions. We found that molecules with a peptide sequence of alternating hydrophobic and hydrophilic amino acids such as VEVE and EVEV self-assemble into flat nanostructures that can be either helical or twisted. On the other hand, nonalternating isomers such as VVEE and EEVV result in the formation of cylindrical nanofibers. Furthermore, we also found that when the glutamic acid is adjacent to the alkyl tail the supramolecular assemblies appear to be internally flexible compared to those with valine as the first amino acid. These results clearly demonstrate the significance of peptide side chain interactions in determining the architectures of supramolecular assemblies.